A prospective randomized controlled trial to study the effect of prenatal yoga on maternal weight gain and psychological stress in pregnancy and its association with pregnancy outcomes - Shukla, Akriti; Prasad, Deeksha; Sharma, K. Aparna; Shainy, Peyyala; Singh, Divya; Sharma, Vinay; Vanamail, P.; Sharma, Gautam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Objective of study was to evaluate the effect of prenatal yoga on maternal gestational weight gain (GWG) and psychological stress in pregnancy (PSS) and to evaluate the effect of prenatal yoga on labour outcomes. Methods: Prospective randomized controlled trial conducted at AIIMS, New Delhi between May 2020-December 2021. Sixty women each were recruited in the yoga and control group. Women in the yoga group attended 60 minutes supervised yoga sessions followed by self-sessions. Women in the control group received routine antenatal care along with 30 minutes per day of walking and dietary counselling. The assessment was done for the weight(WT), dietary intake (D) and perceived stress score (PSS) at the time of recruitment (WT1, D1, PSS1), 28 weeks (WT2, D2, PSS2) and 36 weeks (WT3, D3, PSS3) and the results were then compared. Results: At recruitment all the parameters in both groups were comparable. The difference in mean and difference in percentage in terms of gestational weight gain (GWG) at recruitment and at 36 weeks was statistically significant (p-value=0.027). The per cent weight gain in the Yoga group was significantly low (p value=0.048). The control group experienced more amount of stress both at 28 weeks (p-value = 0.021) and 36 weeks (p-value <0.0001). The difference in mean and difference in percentage in terms of PSS1 and PSS2 (p-value=0.011), PSS2 and PSS3 (p-value=0.0001) PSS1 and PSS 3 (p-value=0.0001). Labour outcomes were comparable between both groups. Conclusions: Yoga helps in controlling excessive GWG and helps prevent many adverse feto-maternal outcomes associated with obesity.